Application of Customer Relationship Management Method On E-Commerce (Case Study : PT Beesge Andalas Perkasa) - Doni Eko Hendro Pramono; Fathurrahman Kurniawan Ikhsan (Institut Bakti Nusantara, 2020)
The data processing process related to sales data and the availability of goods currently running still uses conventional recording, namely the absence of a system that can process data automatically to speed up the Customer Relations Management processing process. (CRM) is a method used to simplify the process of communication between consumers and companies in order to create a sense of comfort in consumers towards the company. One proof of the need for a system desired by the owner of PT Beesge Andalas Perkasa is wanting a system that helps promote and introduce his business and also increase sales without even having to cost a lot in the advertising process. The purpose of this study is to help improve the strategy and loyalty of customers and increase the sales power of PT Beesge Andalas Perkasa